TETAP BERTAHAN DI TENGAH TEKANAN: GAMBARAN RESILIENSI AKADEMIK MAHASISWA - Adrianne Taskia, Frizka; Hastuti, Rahmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Academic resilience refers to students’ ability to persevere, recover, and adapt positively to academic challenges and pressures throughout their studies. This ability is essential because it supports sustained learning engagement and facilitates the management of academic obstacles that may hinder study continuation. Although research on academic resilience is extensive, most studies focus on its relationship with other variables, while studies that specifically describe students’ academic resilience based on its dimensions remain limited, particularly in the Indonesian context. Therefore, this study aims to describe academic resilience among students. This study employed a quantitative approach with a descriptive single-variable design. The sample consisted of 103 students recruited using convenience sampling. Data were collected using the academic resilience scale developed by Hardiansyah et al. (2020), which consists of 27 items covering four dimensions adapted from Cassidy (2015): perseverance, reflecting and adaptive help-seeking, negative affect and emotional response, and adaptive coping. Data analysis was conducted using descriptive statistics by comparing empirical means with hypothetical means. The results indicate that, overall, students’ academic resilience falls into the high category, as shown by a hypothetical mean of 3.6490 and an empirical mean of 2.50. These findings suggest that students demonstrate adequate capabilities in maintaining academic perseverance, reflecting on learning experiences, seeking adaptive assistance, and regulating emotional responses when facing academic stress. Nevertheless, variations across dimensions indicate that certain aspects still require improvement to achieve optimal academic resilience. The findings of this study are expected to serve as a reference for universities in developing more targeted academic resilience development programs.